If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 72x + y = 90 Solving 72x + y = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 72x + y + -1y = 90 + -1y Combine like terms: y + -1y = 0 72x + 0 = 90 + -1y 72x = 90 + -1y Divide each side by '72'. x = 1.25 + -0.01388888889y Simplifying x = 1.25 + -0.01388888889y
| 5x+10=-22 | | 5(5x^2-6x+8)=0 | | 5x-8=2y+5 | | -2(-4x+6)=20 | | C=4c-6 | | 4(5-2n)-3n=4n-85 | | 4x(-7)=(-27) | | 0=5*cos(x) | | (-2x)+5=(-9) | | 8x+112=42 | | 11.4=8y | | (-11)=8x+13 | | 0=5*cosx | | 50/6-1/4=3/8 | | Y^2+4y+4-9y^2=0 | | 7x+17=25 | | 5c+4a+c= | | d=71 | | (2+7)x=15 | | 72(90+-1y)+y=90 | | tan51=x/10 | | 20w^5/35w^4 | | 12y+3=11y+8 | | 3x+8+8= | | 3+5=9-1 | | (6b-24)/(7b-28) | | 2ax^2-(a-4)x-2=0 | | 1/24s^2-54=0 | | 1/24s^2=54 | | 3-2(2+5x)=1(2x+3) | | 3b-8=7+8b | | 6(-2+4x)=-60 |